Strategi Pengembangan Wisata Edukasi Hutan Obat Mbambingan Gunung Kelud Kabupaten Kediri - Rachma Suryani Rahayu; Abu Talkah; Ahsin Daroini (Manajemen Agribisnis: Jurnal Agribisnis, 2023)
This study aims to analyze internal and external factors and formulate alternative development strategies that are appropriate for Mbambingan Mount Kelud Drug Education Tourism. The type of research used in this study is qualitative and quantitative. The sample in this study were 30 tourist visitors (accidental sampling) and 5 tourism management people (purposive sampling). Data analysis used is SWOT analysis and QSPM analysis. Based on the results of the study, it was found that the Mbambingan Mountain Kelud Drug Education Tourism Forest has 5 main focuses of the program namely education, conservation, herbal preservation, community empowerment, and improvement of public health. Internal factors include human resources, marketing, production, finance, research and development and information systems with a total IFE score of 4.19. External factors include the economy, society, technology, competitors and disasters with a total EFE score of 4.36. the most preferred alternative strategy with the highest TAS value of 6.652, namely Cooperation between government agencies and similar companies in tourism-promoting activities, then in second place with a value of 6.554, which is more developing natural potential and managerial human resources, and in third place with value amounting to 6,208 namely by performing maintenance and repairing infrastructure to achieve satisfaction in service.